Endoscopic treatment of gastric varices bleeding with the use of n-butyl-2 cyanoacrylate - Kozieł, Sławomir; Kobryń, Konrad; Paluszkiewicz, Rafał; Krawczyk, Marek; Wróblewski, Tadeusz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Oesophageal varices and gastric varices are naturally-formed, pathological portosystemic shunts that occur in patients with portal hypertension. Gastric varices are responsible for about 10% of variceal bleeding; however, they are also the cause of massive haemorrhage, often with dramatic progress. Aim : To assess the results of endoscopic treatment of gastrointestinal bleeding from oesophageal and gastric varices using tissue glue Histoacryl. Material and methods: From January 2013 to May 2015 170 patients underwent a total of 244 obliterations with the administration of tissue glue due to gastroesophageal varices. We analysed 35 patients who received urgent endoscopic intervention due to life-threatening gastric variceal bleeding. Results: Thirty-five patients underwent 47 endoscopic procedures of haemorrhage management. Immediate haemostasis was achieved in 32 (91.4%) patients. In 3 (8.6%) cases endoscopy failed. In 2 patients a Linton tube was applied before secondary endoscopy. A single trans jugular portosystemic shunt (TIPS) was performed. Permanent haemostasis during the first endoscopy was achieved in 26 (74%) patients. Six (17%) patients presented recurrent bleeding 1–4 days following the initial treatment. Three patients had a splenic artery embolisation performed. One of the embolised patients required surgery, and a splenectomy was carried out. Conclusions : If this kind of therapy is unavailable at the time, it is advised that one of the conventional methods of controlling bleeding is used, introducing basic life support and transporting the patient to a specialist centre with adequate endoscopic facilities, radiological possibilities of endovascular intervention, and surgical treatment of liver transplantation.